2017
DOI: 10.18203/2320-1770.ijrcog20172349
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thyroid and prolactin levels among the women with abnormal uterine bleeding

Abstract: Background: Thyroid disorders are 10 times more common in women than men.1 Menstrual disturbances usually accompany clinical alterations in thyroid function and every clinician would have encountered altered menstrual pattern among women suffering from either hypo or hyper thyroidism. A high serum prolactin level can distrurb the follicular maturation and corpus luteum function, and leads to inhibition of normal pulsatile secretion of gonadotrophin-releasing hormone in hypothalamus resulting in anovulation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In present study majority of the study subjects were in the age group of 36-45 years where as the study done by John JD etal [16] and Pahwa Setal [17] found that AUB was more common in 25-45 years of age group. In our study majority of the women were multiparous 122 (81.33%) and 28 (18.66%) were nulliparous and it was similar to the finding quoted by Pilli etal [18] .…”
Section: Discussionmentioning
confidence: 52%
“…In present study majority of the study subjects were in the age group of 36-45 years where as the study done by John JD etal [16] and Pahwa Setal [17] found that AUB was more common in 25-45 years of age group. In our study majority of the women were multiparous 122 (81.33%) and 28 (18.66%) were nulliparous and it was similar to the finding quoted by Pilli etal [18] .…”
Section: Discussionmentioning
confidence: 52%